2022
DOI: 10.1038/s41598-022-18301-w
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in fruit yield and tolerance to salinity of tomato plants fertigated with micronutrient amounts of iodine

Abstract: Iodine is an essential micronutrient for humans, but its role in plant physiology was debated for nearly a century. Recently its functional involvement in plant nutrition and stress-protection collected the first experimental evidence. This study wanted to examine in depth the involvement of iodine in tomato plant nutrition, also evaluating its potential on salt stress tolerance. To this end, iodine was administered at dosages effective for micronutrients to plants grown in different experimental systems (grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Tomato ( Solanum lycopersicum L.) is one of the most important vegetable crops and is a model plant for stress tolerance research. The harmful effect of salinity in tomato was evident in the range of 100–150 mM NaCl, as shown by a decrease in plant height, dry weight and fruit production (Kiferle et al, 2022). Using PGPB could help to mitigate some abiotic stresses, such as salinity and to reduce the use of chemical inputs in agriculture through direct and indirect mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomato ( Solanum lycopersicum L.) is one of the most important vegetable crops and is a model plant for stress tolerance research. The harmful effect of salinity in tomato was evident in the range of 100–150 mM NaCl, as shown by a decrease in plant height, dry weight and fruit production (Kiferle et al, 2022). Using PGPB could help to mitigate some abiotic stresses, such as salinity and to reduce the use of chemical inputs in agriculture through direct and indirect mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…shown by a decrease in plant height, dry weight and fruit production (Kiferle et al, 2022). Using PGPB could help to mitigate some abiotic stresses, such as salinity and to reduce the use of chemical inputs in agriculture through direct and indirect mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of I related to water deficit is still little reported in the literature; however, reports point to its beneficial effect on the germination and growth of Carthamus tinctorius L. subjected to water deficit [31]. In addition, the effect of this element was also reported for other abiotic stresses, such as salinity [22,26,32] and heavy metals [21].…”
Section: Discussionmentioning
confidence: 99%
“…Other works highlight the ubiquitous role of antioxidant enzymes in mitigating different abiotic stresses [19,20]. Recently, it was demonstrated that the exogenous application of iodine (I) reinforces the antioxidant capacity of lettuce, soybean, and tomato plants by stimulating the activity of the main ROS detoxifying enzymes, i.e., superoxide dismutase (SOD), ascorbate peroxidase (APX), catalase (CAT), and guaiacol peroxide (POD) [18,[21][22][23]. Higher antioxidant enzymatic activity in plants reduces oxidative damage promoted by ROS accumulation under water deficit [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The exogenous application of mineral elements is a vital strategy to alleviate the adverse effects of water deficits on plants. Recently, several studies have recognized that the application of iodine strengthens the antioxidant capacity of soybean (Glycine max), lettuce (Lactuca sativa), and tomato (Solanum lycopersicum L.) plants by stimulating the activity of the main ROS detoxifying enzymes, such as SOD, ascorbate peroxidase (APX), and CAT [7,8,19,20]. Another point to highlight is the nutritional role of iodine in plants, since this element can bind covalently to at least 82 different proteins in the leaves and roots of Arabidopsis thaliana; its presence in micromolar concentrations in the nutrient solution resulted in increased accumulation of plant biomass and timely flowering [21].…”
Section: Introductionmentioning
confidence: 99%